2020
DOI: 10.1136/bmjdrc-2020-001298
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus as a risk factor for compression neuropathy: a longitudinal cohort study from southern Sweden

Abstract: IntroductionCompression neuropathies (CN) in the upper extremity, the most common being carpal tunnel syndrome (CTS) and ulnar nerve entrapment (UNE), are frequent among patients with diabetes mellitus (DM). Earlier studies have shown contradicting results regarding DM as a risk factor for CN. Thus, the aim of the present population-based, longitudinal study was to explore potential associations between DM, CTS, and UNE during long-term follow-up.Research design and methodsA total of 30 466 participants aged 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 50 publications
8
39
0
Order By: Relevance
“…It is possible that the association between diabetes and CTS only exists in specific subgroups (e.g., uncontrolled diabetes). Additionally, our study cannot exclude the possibility of underreporting of CTS, as evidenced by the low prevalence of the condition compared to previous studies [3,4]. Furthermore, the database only collected ICD-9 information on a maximum of three chronic conditions or diagnoses related to the visit per patient.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It is possible that the association between diabetes and CTS only exists in specific subgroups (e.g., uncontrolled diabetes). Additionally, our study cannot exclude the possibility of underreporting of CTS, as evidenced by the low prevalence of the condition compared to previous studies [3,4]. Furthermore, the database only collected ICD-9 information on a maximum of three chronic conditions or diagnoses related to the visit per patient.…”
Section: Discussionmentioning
confidence: 86%
“…In the hyperglycemic state, excess metabolism of glucose leads to intracellular sorbitol accumulation in the neuron and the adjacent Schwann cells. Ultimately, this leads to axonal degeneration and segmental demyelination of the nerve, making it more vulnerable to compression with a lower threshold to develop CTS [4]. Studies reporting on the association between DM and CTS vary greatly on the magnitude based on the geographic location where the study took place; the association was reported to be lower in populationbased studies than in hospital-based studies [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Rydberg, et al did a longitudinal study to explore potential associations between diabetes mellitus and entrapment neuropathies during long term follow up and found hyperglycemia to affect the median and ulnar nerves differently. 8 Kocer et al examined different methods of studying sural nerve conduction in a group of patients with impaired glucose tolerance supporting the idea that impaired glucose tolerance is a transitional state before diabetes and also the importance of dorsal sural nerve latencies for early detection of neuropathy. 9 Ogawa et al reported a case of a 48-year old man with a 14-year history of type 2 diabetes with proliferative diabetic retinopathy and distal symmetrical diabetic polyneuropathy and within a span of 8 months, he sub acutely developed difficulty in both shoulder movement and trouble standing up from a squatting position with severe bilateral shoulder and thigh pain.…”
Section: Discussionmentioning
confidence: 91%
“…This effect may be related to several factors. For instance, obesity, Diabetes Mellitus and smoking have been reported as risk factors for Ulnar Neuropathy [ 10 , 29 ]. Although there is large inter-individual variability in weight loss following regular exercise training [ 30 ], it is conceivable that the ~4.5 h training/week of the wheelchair athletes included in the present study has contributed to the maintenance of what is considered a healthy body mass.…”
Section: Discussionmentioning
confidence: 99%